Relative sets and rough sets - Mousavi, Amin; Jabedar-Maralani, Parviz (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, by defining a pair of classical sets as a relative set, an extension of the classical set algebra which is a counterpart of Belnap's four-valued logic is achieved. Every relative set partitions all objects into four distinct regions corresponding to four truth-values of Belnap's logic. Like truth-values of Belnap's logic, relative sets have two orderings; one is an order of inclusion and the other is an order of knowledge or information.
Keywords: rough sets; set theory; data analysis; multi-valued logic; interval sets; knowledge representation